Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1186/1471-2180-13-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of methicillin-resistant Panton-valentine leukocidin positive staphylococcus aureus clones disseminating in Tunisian hospitals and in the community

Abstract: BackgroundThe spread of MRSA strains at hospitals as well as in the community are of great concern worldwide. We characterized the MRSA clones isolated at Tunisian hospitals and in the community by comparing them to those isolated in other countries.ResultsWe characterized 69 MRSA strains isolated from two Tunisian university hospitals between the years 2004-2008. Twenty-two of 28 (79%) community-associated MRSA (CA-MRSA) strains and 21 of 41 (51%) healthcare-associated MRSA (HA-MRSA) strains were PVL-positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 43 publications
3
56
0
2
Order By: Relevance
“…Similar results were reported by Ramdani-Bouguessa et al [49] who reported that pvl was the most detected toxin gene (72%) of the tested clinical isolates. Similar results were also reported from a Tunisian study [50] where 79% of the community acquired MRSA contained the pvl gene while 51% of the health care associated MRSA infections contained the pvl gene. However, as with distribution of antibiotic resistance, toxin distribution varied between studies from different areas of the world.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar results were reported by Ramdani-Bouguessa et al [49] who reported that pvl was the most detected toxin gene (72%) of the tested clinical isolates. Similar results were also reported from a Tunisian study [50] where 79% of the community acquired MRSA contained the pvl gene while 51% of the health care associated MRSA infections contained the pvl gene. However, as with distribution of antibiotic resistance, toxin distribution varied between studies from different areas of the world.…”
Section: Discussionsupporting
confidence: 87%
“…For instance, following AluI digestion, 61 MRSA isolates were clustered in genotype C rather than genotype A. Similar changes in the cluster arrangement were observed when a dendrogram was constructed for MRSA isolates restricted with Cfo I where the majority of isolates (50) were clustered in genotype A rather than genotype D.…”
Section: Discussionsupporting
confidence: 53%
“…However, the PVL marker for CA-MRSA was disputed in recent years, not only because the PVL-positive rates in CA-MRSA recovered from certain regions were Ͻ10% (27), but also because HA-MRSA was also confirmed to carry the PVL genes. Mariem et al (9) reported that 21 of 41 (51%) HA-MRSA strains were positive for PVL in Tunisian hospitals, and another study reported that 5.7% of the HA-MRSA isolates were PVL positive in Asian countries (10). The increasing prevalence of PVL-encoding HA-MRSA is a serious concern that may worsen MRSA infections.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing carriage of PVL genes in a certain MRSA lineage may result from the spread and transfer of PVL-encoding phages. Using the available PVL phage-specific primers (14)(15)(16)18), we characterized 59 PVL-encoding phages belonging to various phage groups, whereas the remaining phages in 15 PVL-positive MRSA isolates were not determined, which would indicate the existence of new PVL-encoding phages that have yet to be characterized, such as the recently characterized PVL phages ⌽IND772 and ⌽7401 (9,29). We also determined that hospital-onset HA-MRSA isolates were colonized mainly by PVL phages with high infectivity, such as ⌽7247PVL, ⌽SLT, and ⌽Sa2958, which might explain the increasing prevalence of PVL in HA-MRSA isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are no data about the presence of MRSA CC398 in Muslim countries, in which pork is not consumed. Thus, in Tunisia, some reports have described the detection of different clonal lineages of MRSA in samples from human and animal origins (Ben Nejma et al, 2013;Ben Slama et al, 2011;Gharsa et al, 2012;Kechrid et al, 2011;Mariem et al, 2013). However, no MRSA ST398 isolates have been identified in hospitals in Tunisia.…”
Section: Introductionmentioning
confidence: 99%